Avaliação da Moringa oleífera Lam na remoção do corante remazol ultra amarelo RGBN - Cézar, Katiusca Lima (2020)
Synthetic dyes are one of the most consumed products in the textile sector, generating toxic effluents, with chemical residues of different compositions. Conventional biological treatment processes demonstrate little effectiveness in removing these chemical compounds. The Moringa oleifera Lam is a plant native from India that has adapted well to the hot and dry climate, it has been studied for presenting potential capacity to replace the commercial coagulants in the effluent treatments. This work proposes a low cost alternative in the treatment of dyes that remain persistent in textile effluents after conventional treatments. The objective of this work was to evaluate the efficiency of this bioadsorber (Moringa oleifera Lam) in the removal of the remazol ultra yellow RGBN dye and to monitor the toxicity of the residual concentration solutions after the experiment. For this purpose, the surface of the adsorbent was characterized before and after the interaction with the dye. The Infrared spectrum showed peaks characteristic of specific groups of the adsorbent as in 1748 (cm-1) corresponding to the -COOH of carboxylic acids and carbonyl group of hemicellulose. A factorial design 23 with a central point was performed to evaluate the optimal experimental conditions. The factors studied were agitation, mass and granulometry. Kinetic studies and isotherm models were used to determine the adsorption capacity. In addition, toxicity studies with lettuce seeds (Lactuca sativa) and DQO were carried out. The planning results showed that agitation at the upper level (450 rpm), together with the granulometry at the lower level (250 µm) provided greater removal of the remazol ultra yellow RGBN dye. The Langmuir o isotherm and the pseudo-second order method showed the best adjustments considering the values R2 (0.9978) and (0.9966) respectively. Root inhibition rates were significant, demonstrating no toxicity in the tests. The DQO analysis indicated that the use of a small amount of Moringa oleifera Lam is efficient in the removal process, without changing the oxygenation level in the treated effluents. The results obtained in the experiments involving the adsorption of the dye showed efficiency above 80% of the bioadsorber Moringa oleifera Lam in natura.